Electrohydrodynamic instabilities of multi-fluid flows in microfluidic systems - Ding, Zijing (2016)
In the last decade, the interfacial instability and mixing enhancement in microfluidic flow systems have attracted much attention . The control of interfacial instability is very crucial in multi-phase flow systems, such as the droplet production systems. In microfluidic systems, rapid mixing has been a long-standing challenge for the small Reynolds number in which turbulence will not occur. Previous studies have demonstrated that rapid mixing can be achieved using an electric or magnetic field. In all of these systems, it is rather important to know the instability threshold. This thesis devotes to the discussion of the effects of electric field on the interfacial instability and electro-mixing in an annulus channel. Based on the evidence that the wave length is often much longer than the mean thickness of a fluid layer, Chapter 3 investigated the linear and nonlinear dynamics of a perfectly conducting liquid film coating on a metal fiber modulated by the gravity effect in the framework of longwave theory. A radial electric field was imposed between the inner fiber and a outer electrode and the dynamics of the gas phase was neglected. It was found that the electric field can either reinforce or suppress the interfacial instability by manipulating the distance between the outer electrode and the inner fiber. In Chapter 4, the interfacial instability of two coflowing annular liquids in a radial electric field has been discussed when taking into account the dynamics of the outer layer. Unlike the assumption made in Chapter 3 that the liquids were perfectly conducting, the two immiscible liquids in Chapter 4 were leaky-dielectrics. Moreover, in Chapter 4, interfacial instability of two immiscible leaky dielectric fluids was examined in the full range of wave numbers. It was found that in such a system, the interfacial instability can be either caused by the so-called Rayleigh-Plateau mechanism or the viscosity stratification between the two layers. A detailed study of the effects of normal and tangential Maxwell stresses on the two kinds of interfacial instabilities demonstrated that both of them can either stabilize or destabilize the interface, depending on the electrical properties of the two liquids. However, the two studies in Chapters 3-4 provided evidences that the interfacial instability caused by the Rayleigh-Plateau mechanism can be modulated by the external electric field and thereby control the formation of droplets. Electro-convection was investigated in Chapters 5-6. Chapter 5 discussed the electrohydrodynamic instability of an annular liquid layer with a radial electrical conductivity gradient which was developed from the imposed radial electric field. Chapter 6 studied the instability in two miscible liquids with an electrical conductivity stratification wherein a uniform axial electric field was imposed. Studies in the two chapters demonstrated that the instability is triggered by the dielectrophorectic effect. Study in Chapter 5 showed that the critical unstable mode in the annular liquid layer could be either stationary or oscillatory, dependenting on the conductivity gradient. However, in the two-miscible two flows, the critical unstable mode is always oscillatory. Furthermore, results in Chapter 5 indicated that the flow is least stable for a moderate conductivity gradient whereas Chapter 6 demonstrated that the flow is always more unstable for a larger contrast in conductivity. It should also be pointed out that, in Chapter 5, the critical instability could be reinforced by a weak shear flow; while the critical instability is always impeded by the shear flow in Chapter 6. A summary of the four Chapters 3-6 was made, and perspectives of future works built upon these works have been proposed in Chapter 7.